(untitled) (African Multidisciplinary Journal of Research, 2025)
The Church has continued to embrace the use of online media platforms with a view of reaching out to a wider audience. The Anglican Church of Kenya (ACK) through her leadership has been on the forefront since 2017 in championing the use of online media platforms due to decreasing youth enrolment in church, which stood at 10% in 2017. This is happening at a time when the number of youth who have subscribed to online media platforms is also increasing. The study examined the adoption of online church platforms and participation of youth in an ACK deanery, the involvement of the youth in planning for online church service and the challenges encountered by the youth in online church service. The study employed Connectivism Learning Theory by George Siemens (2005) to understand how technology and innovations are adopted at ACK, St. Andrew’s and St. Monica’s Mugumo-ini parishes. The study reviewed empirical data on online church services, youth involvement and challenges of online platforms in enhancing participation among the youth. The study adopted a mixed approach method and utilized a descriptive research design. The target population was (1055) and a sample of 15% (159) which was proportionately and purposively selected. A semi-structured questionnaire was administered to members of Kenya Anglican Youth Organisation (KAYO) and parents/guardians, while FGD was carried out among church leadership, whereas the bishop was interviewed. A pilot study was conducted in Memorial Parish and was considered in the final study. This was done by calculating Pearson’s correlation and Cronbach Alpha, which met the 0.7 threshold. Face validity was carried out to ensure the accuracy of the questionnaire and interview schedule. Data collected was then analysed descriptively and thematically. The findings of the study showed that the church adopted Facebook at (84.6%), Twitter (0%), YouTube (38.5%), and WhatsApp (61.5%). On the involvement of the youth, the study found that the church involved the youth in technical support 61.5%. Challenges faced by the youth in online church participation included distraction by other social media (61.6%), internet connectivity at 23% and cost of data at 15.4%. The study found that overall online church attendance among the youth stood at 38.5%. The study’s overall recommendations were that; the church ought to utilize YouTube and Facebook for live streaming, run online church services for the youth for a maximum of 30 minutes, and use WhatsApp for online bible study services. Further, the study recommends that the church should offer meaningful involvement of the youth and its leadership rather than limiting them to technical support. These may include offering strategic training on innovative online technologies to church leadership and monitor online youth participation by assessing statistics after each online service/activity.